2010
DOI: 10.1021/jp105699s
|View full text |Cite
|
Sign up to set email alerts
|

Double Freezing of (NH4)2SO4/H2O Droplets below the Eutectic Point and the Crystallization of (NH4)2SO4 to the Ferroelectric Phase

Abstract: This paper presents the differential scanning calorimetry (DSC) results obtained from measurements of single droplets of different subeutectic concentrations (<40 wt % (NH4)2SO4) and diameters of 1-1.5 mm. The measurements show that despite the fact that the freezing of the droplets takes place below the eutectic temperature of Te ≈ 254.5 K, a phase separation into ice and a residual freeze-concentrated solution occurs. The residual solution is formed by the expulsion of NH4+ and SO42- ions from the ice lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(56 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…Cho et al (2002) argued that kinetic limitations leading to supercooled solutions could not explain the observations, because the amount of liquid closely followed the temperature during warming periods toward the eutectic temperature. Freezing of emulsions that resemble water droplets in the atmosphere can be kinetically hindered so that a meta-stable liquid phase exists well below the eutectic temperature (Koop et al, 2000;Bogdan, 2010). Using surface-sensitive, synchrotron-based X-ray spectroscopy, Křepelová et al (2010a) found no evidence for liquid on the surface of frozen solutions of NaCl below the eutectic.…”
Section: Below the Eutectic Compositionmentioning
confidence: 99%
“…Cho et al (2002) argued that kinetic limitations leading to supercooled solutions could not explain the observations, because the amount of liquid closely followed the temperature during warming periods toward the eutectic temperature. Freezing of emulsions that resemble water droplets in the atmosphere can be kinetically hindered so that a meta-stable liquid phase exists well below the eutectic temperature (Koop et al, 2000;Bogdan, 2010). Using surface-sensitive, synchrotron-based X-ray spectroscopy, Křepelová et al (2010a) found no evidence for liquid on the surface of frozen solutions of NaCl below the eutectic.…”
Section: Below the Eutectic Compositionmentioning
confidence: 99%
“…It is seen in figure 1(a) that the millimeterscaled droplets produce sharp freezing peaks, whereas in figure 1(b) the micrometer-scaled droplets produce broad bellshaped freezing peaks which are due to the freezing of a large number ( 10 5 ) of size-distributed droplets. In both cases, in the warming thermograms (lower lines) there are two melting events which are produced by melting of the eutectic solid mixture of ice/(NH 4 ) 2 SO 4 (colder melting peaks at constant temperature) and pure ice, respectively [17]. It is also seen that as the concentration increases, the peak melting temperature of ice approaches the eutectic melting of ice/(NH 4 ) 2 SO 4 .…”
mentioning
confidence: 91%
“…We prepared 5,10,15,20,25,28,30,33,35, and 38 wt% (NH 4 ) 2 SO 4 solutions by mixing 99.99% (NH 4 ) 2 SO 4 crystals (Sigma Aldrich) with the corresponding amount of ultrapure deionized water. Emulsions were prepared according to a well known and widely used emulsification technique described elsewhere [5,9,17,18]. Briefly, the oil phase for the preparation of emulsions was prepared by mixing 80 wt% Halocarbon 0.8 oil (Halocarbon Products Corp.) and 20 wt% lanolin (Sigma Aldrich).…”
mentioning
confidence: 99%
See 2 more Smart Citations